PRESIDENTIAL ADDRESS - Fungicides in crop health securityâ€“the road ahead - THIND, T.S. (Indian Phytopathology, 2012)
I am highly grateful to the members of the Indian Phytopathological Society for giving me the honour to serve the Â Society as its President for the year 2011. For my presidential address, I have chosen to discuss about the role of fungicides in ensuring crop health security by managing devastating diseases in agricultural crops. Plant diseases are estimated to cause yield reductions of almost 20% in the principal food and cash crops worldwide. Of the over 100,000 described species of fungi in the world, approximately 20,000 produce one or more diseases in various plants. Over the past 150 years, much has been learnt about the control of plant diseases and several complementary approaches such as cultural methods, biological methods, chemical control and regulatory measures were developed for their control. Depending on the crop, the disease and the availability of control methods, a different set of approach is employed.